Internet of Things to Improve the Quality of Islamic Education - Safitri, Hana Ayu; Maksum, Muh.Nur Rochim (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
The Internet of Things is a wireless network that connects one object to another using the internet that does not require interaction between humans. Internet of Things is one of the trends to apply it in the world of education. The purpose of the study is to analyze the use of Internet of Things technology to improve the quality of Islamic education. The method used in this study is library research by collecting literature related to the use of IoT in educational institutions. The result of this research is that sensors connected to IoT in Islamic educational institutions strive to collect data in a very fast time, automatic management of facilities so that they are more efficient.